(untitled) (Nexo Revista Científica, 2021)
The article considers the methodology of forming the matrix of A-parameters of a rail line, represented by a multi-pole equivalent circuit. It is shown that when using a four-pole equivalent circuit of a rail line in case of violation of the equipotentiality of the circuit, it is impossible to take into account the flow of current along bypass paths, along the earth path, and the influence of adjacent track circuits. A multi-pole equivalent circuit of a rail line is represented as a 2x4 pole, in the rail lines of which self-induction EMF sources are included, and an earth path is used as the second wire. An equivalent multi-pole of equivalent circuit is represented by two groups of poles – at the input and output of the rail line, including one common (ground). The parameters of all elements of the equivalent multi-pole circuit are presented in the form of matrices, which makes it possible to analyze the state of the rail lines when changing the primary parameters of the rail multi-pole in a wide range. Using Kirchhoff’s laws and solving a system of ordinary differential equations, the A-parameters of a rail multi-pole are obtained.